Virtual Dissections and their Acceptance by Biology Teaching Students in the Czech Republic - Havlíčková, Veronika; Bílek, Martin; Šorgo, Andrej (Scientia in educatione, 2018)
Virtual dissections, performed via computer simulations as an alternative to hands-on dissections, have been slowly finding its place within lessons of Biology as a general educational subject. This fact has been demonstrated by many, predominantly international, studies, which were subject to our investigation already in the survey part of our research; the findings served as a basis for further questionnaire survey examining the attitudes of biology teacher trainees towards the use of virtual and hands-on dissections in the Czech Republic. The aim of the survey was primarily to identify the attitude of pre-service biology teachers concerning the use of virtual and hands-on dissections, their experience with these teaching applications, and their preferences with regard to these options. An analysis of the obtained indicates that most of the students have had experience with hands-on dissections. However, the students’ attitudes confirms their preference towards using virtual dissections, although the performance of hands-on dissections is not to be eliminated completely.